Perlindungan Konsumen Terhadap Kasus Vaksin Palsu Dalam Perspektif Undang-Undang - David Greacy Geovanie; Kadek Bobby Reza Arya Dana (Jurnal Locus Delicti, 2021)
This research aims to explain the form of government responsibility as health providers are subject to the circulation of fake vaccines, the form of responsibility of business pelau (producers) against fake vaccine victims. The benefits of this research consist of theoretical benefits and practical benefits. The method used is normative. Results pembahsan is a form of government responsibility as health penyenggra against the circulation of fake vaccines is to do coaching and supervision in the framework of consumer protection. The liability of business actors against fake vaccine victims can be done by way of refund, replacement of goods and / or services of a similar or equivalent value, as well as health care and / or providing compensation in accordance with applicable laws and regulations